Gestión de talento humano y su incidencia en el desarrollo profesional de los docentes de la Unidad Educativa Barreiro, Babahoyo, Los Ríos. Ecuador - Vilche Valverde, Monica Efigenia (2022)
The objective of this research was the Management of Human Talent based on Motivation to improve the professional development of teachers of the "Barreiro" educational unit, for which the following question was formulated: How does Human Talent Management affect the development professional of the teachers of the educational unit "Barreiro"? Since it has been observed that among the teachers of this educational establishment there is disagreement due to the so-called talent management, which is exercised by the leader of this institution and also by the administrative staff who work here. Because the decisions you make based on the teaching-learning process do not favor their professional development Regarding the methodology, we have a non-experimental research design, whose population is 48 teachers. For the data collection, the survey technique was used and the questionnaire as instruments. Among the conclusions obtained, it was possible to observe that: It was possible to identify the factors that affect the professional development of the teachers of the "Barreiro" educational unit, which must be motivated through an adequate Human Talent Management based on the Motivation to achieve positive results. It was concluded that in the Educational Institution it is necessary to continuously carry out training programs on issues related to the management of human talent and all the benefits that good management can grant, not only to the institution, but also allow teachers to enhance their develop professional.